HUBUNGAN KARAKTERISTIK LAHAN DENGAN PRODUKTIVITAS TBS (Studi Kasus pada PT. Perkebunan Nusantara VIII Cimulang, Bogor) - Komarsa Ganda Sasmita; Basuki Sumawinata; Sry Nurmala (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Oil palm (Elaeis guineensis Jacq) is an important crop for Indonesia as one of non fuel export commodities. Development, improvement of quality and productivity of oil palm is influenced by a lot of factors, among others are land characteristics. This research was aimed to know the relationship between oil palm productivity and physical land characteristic including soil, slope and the crop age. The results of this research were expected to be useful to improve oil palm productivity and the oil palm plantation development.This research was done within the site of PT. Perkebunan Nusantara VIII at Cimulang, Bogor. In this research, analyzing correlation between productivity of blocks that have homogenous land characteristic with physical land characteristic parameter including soil and slope. Block with homogenous land characteristic was block which 75% or more of it’s area had similar characteristics. These blocks were determined by overlying block map, slope map and soil map. The result show that were 20 homogenous blocks out of all the 38 blocks of the site the PT. Perkebunan Nusantara VIII at Cimulang. Average production was depend on crop age. At study areas, the highest average fresh fruit bunch production obtained from plants 5 years, which was equal to 22.87 tons acre-1 year-1 and the lowest average fresh fruit bunch production obtained from plants 3 years, which was equal to 0.66 tons acre-1 year-1.  Based on soil, the highest average fresh fruit bunch production obtained from the SPT 11 (Typic Eutrudox), which was equal to 12.54 tons/acre/year and the lowest average fresh fruit bunch production obtained from SPT 1 (Oxic Dystropept), which was equal to 9.51 tons/acre/year. Based on slope class, the highest average fresh fruit bunch production obtained from block with slope class B (8-15%), which was equal to 12.54 tons/acre/year, and the lowest average production was equal to 9.98 tons/acre/year from the slope class.